2010
DOI: 10.17221/2981-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Biologically active substances of bird skin: a review

Abstract: Bird skin has a number of specific properties. The uropygial gland is a significant skin gland in many species. The secretion of this gland is particularly necessary for maintaining physical characteristics, including feather waterproofing. In some bird species this gland secretion has a repellent effect against potential mammalian predators; in other species it affects the final colour of feathers. In the investigated species of storks (genus Ciconia), secretions of the uropygial gland have been found to be m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 51 publications
0
19
0
1
Order By: Relevance
“…Interestingly, T. dimidiata females were not attracted to volatiles from live insect or to MG extracts, but they were attracted to two compounds (octanal and 6‐methyl‐5‐hepten‐2‐one) present in the extracts, when these compounds were evaluated individually. Several compounds, including octanal and 6‐methyl‐5‐hepten‐2‐one, detected in the exocrine glands of triatomines have also been found in the odour of birds and mammals (Meijerink et al , 2000; Guerenstein & Guerin, 2001, 2004; Syed & Leal, 2009; Rajchard, 2010), common hosts of triatomines. Thus, the attraction of T. dimidiata females and males, to these compounds could be interpreted as responses to host cues.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, T. dimidiata females were not attracted to volatiles from live insect or to MG extracts, but they were attracted to two compounds (octanal and 6‐methyl‐5‐hepten‐2‐one) present in the extracts, when these compounds were evaluated individually. Several compounds, including octanal and 6‐methyl‐5‐hepten‐2‐one, detected in the exocrine glands of triatomines have also been found in the odour of birds and mammals (Meijerink et al , 2000; Guerenstein & Guerin, 2001, 2004; Syed & Leal, 2009; Rajchard, 2010), common hosts of triatomines. Thus, the attraction of T. dimidiata females and males, to these compounds could be interpreted as responses to host cues.…”
Section: Discussionmentioning
confidence: 99%
“…They also indicated that, although recognizable, lipids associated with the feathers of deceased birds are generally only present in trace amounts. Nonetheless, as in vivo epidermis or uropygial ( preen) gland secretions consist of wax esters, triacylglycerols and cholesterol (Rajchard, 2010) and vary according to species, season, health, and nutrition (Jacob, 1976), careful consideration is required in each case.…”
Section: Contaminants and Controlsmentioning
confidence: 99%
“…A prime cause of organism illness and death involves bacteria, against which animals and plants have developed a wide variety of defensive strategies. Apart from physical barriers, several antimicrobial substances are produced by the innate immune system to fight bacterial infections (reviewed in Jenssen et al, 2006;Rajchard, 2010). In addition, several types of animal behaviours like preening may also diminish the probability of infection by microorganisms (Moore, 2002).…”
Section: Introductionmentioning
confidence: 99%